An integrative analysis of DNA methylation and gene expression to predict lung adenocarcinoma prognosis - Xu, Liexi; Huang, Zhengrong; Zeng, Zihang; Li, Jiali; Xie, Hongxin; Xie, Conghua (Frontiers in Genetics, 2022)
Background. Abnormal DNA methylation in gene promoters is an important feature in lung adenocarcinoma (LUAD). However, the prognostic values of DNA methylation remain to be further explored. Objectives. We sought to explore DNA methylation characteristics and develop a quantifiable criterion related to DNA methylation to improve survival prediction of LUAD patients. Methods. Illumina Human Methylation450K array data, level 3 RNA-seq data and corresponding clinical information were obtained from TCGA. Cox regression analysis and Akaike information criterion were used to construct the best-prognosis methylation signature. Receiver operating characteristic curve was used to validate the prognostic ability of the DNA methylation related feature score. qPCR was used to detect the transcription levels of identified genes upon methylation. Results. We identified a set of DNA methylation feature composed of 11 genes (MYEOV, KCNU1, SLC27A6, NEUROD4, HMGB4, TACR3, GABRA5, TRPM8, NLRP13, EDN3 and SLC34A1). The feature score calculated according to DNA methylation feature was independent from tumor recurrence and TNM stage in predicting the overall survival. Of note, the combination of this feature score and TNM stage provided a better overall survival prediction than either of them individually. The transcriptional levels of all the hypermethylated genes were significantly increased after demethylation, and the expression levels of 3 hypomethylated proteins were significantly higher in tumor tissues compared with normal ones as immunohistochemistry data from the Human Protein Atlas indicated. Our results suggested that these identified genes with prognostic feature were regulated by DNA methylation in their promoters. Conclusions. Our studies demonstrated the potential application of DNA methylation markers in the prognosis of LUAD.